PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS DEBITUR PT. BANK PERKREDITAN RAKYAT NUSANTARA BONA PASOGIT 12 - Rudy Bodewyn Mangasa Tua (Prodi Manajemen Fakultas Ekonomi Universitas Pamulang, 2016)
This thesis aims to find out the magnitude of the influence of marketing mix to the Debtor on the Loyalty of PT. Bank Perkreditan Rakyat Nusantara Bona Pasogit 12 in Serpong. The methods used in this research is quantitative descriptive survey method with the korelasional approach that aims to analyze the influence of free and bound variables, with the techniques of examining a sample of part of the population. The Data used is primary data. The results showed that simultaneously the indicator product, Office Networks, promotion, pricing, HUMAN RESOURCES, physical evidence and simultaneously Process a significant effect against the debtor Loyalty satisfaction BPR. BPR products partially affect the loyalty of Debtors was significantly, partially BPR office network does not affect the debtor's Loyalty, promotions partially also does not affect the loyalty of the debtor, the price partially affect the loyalty of Debtors was significantly partially, HR affect the loyalty of Debtors was significantly partially Physical, the evidence did not affect the debtor's Loyalty, and the process of partially affect the loyalty of the debtor in a significant way. Keywords: Marketing Mix, The Loyalty Of The Debtor.